2009
DOI: 10.1002/adma.200901344
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Self‐Assembly of Photoluminescent Oligo(p‐Phenylenevinylene) Derivatives in Liquid Crystals: An Effective Strategy for the Macroscopic Alignment of π‐Gels

Abstract: Aligned photoluminescent fibers are formed by the self assembly of an oligo‐(p‐phenylenevinylene) derivative (OPV) in oriented liquid crystals (see figure). The aligned fibers of OPV show polarized yellow emission in the direction of the long axis of fibers. New types of electro‐optical and photonic systems can be visualized in the future as the polarized luminescence of these fibers is combined with the dynamic properties of the liquid crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 84 publications
0
46
0
Order By: Relevance
“…Examples where such control is highly benefi cial or even crucial for device performance are in optoelectronic devices [8][9][10] and in tissue engineering, where a macroscopically organized polymer scaffold is necessary for the growth of highly aligned tissue, such as muscle fi bers and neural tissue. In nonaqueous solvents (bulk thermotropic liquid crystals), the concept of LC templating was demonstrated successfully [ 10,[26][27][28][29][30][31] but in aqueous solutions unidirectional alignment at large length scales is rarely realized, let alone locally controlled. [ 9,11 ] These techniques all have demonstrated their benefi ts, but also strong limitations such as incompatibility with (aqueous) soft matter, low susceptibilities, and/or poor spatial control across multiple length scales.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Examples where such control is highly benefi cial or even crucial for device performance are in optoelectronic devices [8][9][10] and in tissue engineering, where a macroscopically organized polymer scaffold is necessary for the growth of highly aligned tissue, such as muscle fi bers and neural tissue. In nonaqueous solvents (bulk thermotropic liquid crystals), the concept of LC templating was demonstrated successfully [ 10,[26][27][28][29][30][31] but in aqueous solutions unidirectional alignment at large length scales is rarely realized, let alone locally controlled. [ 9,11 ] These techniques all have demonstrated their benefi ts, but also strong limitations such as incompatibility with (aqueous) soft matter, low susceptibilities, and/or poor spatial control across multiple length scales.…”
mentioning
confidence: 99%
“…In nonaqueous solvents (bulk thermotropic liquid crystals), the concept of LC templating was demonstrated successfully [ 10,[26][27][28][29][30][31] but in aqueous solutions unidirectional alignment at large length scales is rarely realized, let alone locally controlled. This approach has numerous advantages: (i) it does not depend on specifi c interactions between the assembly and the template and thus it can be applied to a wide range of materials; (ii) any desired (hierarchical) structure can be imprinted on the substrate and reproduced in the assembly; (iii) the desired product can be (chemically) modifi ed after organization (in our case to generate optically active π-conjugated polymers); and (iv) the template can be removed which only leaves the functional material on the substrate.…”
mentioning
confidence: 99%
“…In our previous studies, a cyanobiphenyl LC mixture, MCB , was used for alignment control of photoluminescent and polymerizable fibers . MCB has been prepared as a liquid crystal to combine with 1.…”
Section: Resultsmentioning
confidence: 99%
“…For example, liquid crystals, external stimuli, and ordered surfaces were used to attain macroscopic alignment of self‐assembled fibers. It was also demonstrated that oriented fibrous aggregates showed significant functions such as efficient carrier transport and polarized photoluminescence …”
Section: Introductionmentioning
confidence: 99%
“…Hence, FRET studies have been conducted in micelles [12], reverse micelles [13,14], vesicles [15], liposomes [16], ionic liquids [17,18], supramolecular assemblies [19], DNA [20], quantum dots and cyclodextrins [21], etc. Recently, there has been a spurt in energy transfer studies aimed for the development of novel white light emitting organogels like [22][23][24][25][26][27].…”
Section: = +mentioning
confidence: 99%